USM VICE-CHANCELLOR: ACCORD PEOPLE THE RESPECT AND AVOID ‘SYUBHAH’ CONDUCTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, September 2015 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato’ Dr Omar Osman advised the latest batch of students enrolling into USM to always have respect for each other and to avoid from being involved in ‘syubhah’ (without any certainty) conducts which could ruin society and the country.